Effect of alginate coating on the physico-chemical and microbial quality of pansies (Viola × wittrockiana) during storage - Fernandes, Luana (2018)
Edible ﬂowers, such as pansies, are becoming more popular, but they are highly perishable. So, postharvest technologies are needed, being edible coatings a good alternative. Thus, the aim of this study was to evaluate the effect of alginate coating on physico-chemical and microbiological quality of pansies during cold storage (4 ºC for 0, 7, 14, 21 days). Coated pansies maintained good appearance until 14 days of storage, 7 days more than uncoated ones. Flavonoids, hydrolysable tannins and monomeric anthocyanins, as well antioxidant activity, were higher in coated pansies when compared to uncoated ones, on all assayed storage times. Furthermore, after 14 days of storage, uncoated pansies presented microorganism counts higher than coated, namely yeasts and moulds, suggesting an effective barrier protection of the alginate coating treatment. In summary, alginate coating has potential for extending shelf-life and improving physico-chemical and microbiological quality of pansies.